2021
DOI: 10.47338/jns.v10.989
|View full text |Cite
|
Sign up to set email alerts
|

Congenital pouch colon with colonic atresia- An unusual embryological association: A case report

Abstract: Background: Congenital pouch colon (CPC) is a rare variant of high anorectal malformation. More and more varied associations of CPC with other entities are being added to the literature. Case presentation: A 1-day-old male baby presented to the emergency room with marked abdominal distension and absent anal opening. On exploration, the baby was found to have CPC (Type 2) with colonic atresia. This association has not been reported in English literature. Conclusion: This is a report of a case of type 2 CPC with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Focusing on CA signs and symptoms, a retrospective study done in India concluded that the common presenting signs and symptoms were distended abdomen, constipation, and bilious vomiting [9]. Moreover, meconium-stained penis and dehydration can be presented in CA patients [10]. Our patient presented with abdominal distention, bilious vomiting, jaundice, and high-grade fever.…”
Section: Discussionmentioning
confidence: 70%
See 4 more Smart Citations
“…Focusing on CA signs and symptoms, a retrospective study done in India concluded that the common presenting signs and symptoms were distended abdomen, constipation, and bilious vomiting [9]. Moreover, meconium-stained penis and dehydration can be presented in CA patients [10]. Our patient presented with abdominal distention, bilious vomiting, jaundice, and high-grade fever.…”
Section: Discussionmentioning
confidence: 70%
“…Regarding the management of CA, staged surgery was preferred over primary anastomosis due to the potential risk of primary bowel anastomosis [10]. Nowadays, primary anastomosis is the procedure of choice for uncomplicated CA.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations